Traffic congestion detection and optimizing traffic flow using object detection, optical flow and fluid dynamics - Hossain, Md. Shahriyar; Bhuiyan, Md. Imtiaz; Dulali, Marjahan Akther (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.